Gas flux distribution in mineral springs and tectonic structure in the western Eger Rift - Weinlich,F.H.; Tesar,J.; Weise,S.M.; Brauer,K.; Kampf,H. (Journal of the Czech Geological Society, 1998)
The gases of more than 70 mineral springs and mofettes (cold dry CO2 gas vents) were investigated for gas flux, gas composition and 3He/4He ratios in the western part of the Eger Rift. Both regional gas flux and gas composition pattern are controlled by the tectonic structure. Four separate main gass escape centres could be detected, partly with gas fluxes of more than 150 m3/hr of free gas: Frantiskovy Lazne/Cheb Basin, Marianske Lazne, Konstantinovy Lazne and Karlovy Vary. The very similar gases of the gas escape centres are > 99 vol.% CO2-rich. Isotopically heavy CO2 and high mantle derived helium proportions indicate the magmatic origin of these CO2 rich gases. As a result of gas fractionation by CO2 solution and HCO3- formation the N2 contents in the gas phase increase in the margin areas with lower gas flux. According to a first estimates, the entire gas flux (natural flux) in the western part of the Eger Riftr lies around a minimum of 5.31 million m3/a free gas, including dissolved CO2 and HCO3- of 8.13 million m3a. The opposite dip of the main faults of the Eger Rift forms a Y-shaped structure and splits the gas flux about 15km below the surface, forming a CO2-free zone between them. The borders of this zone correspond to the position of the Eger Rift main fault, the southern border to the Litomerie deep fault. The Eger Rift is shifted on younger NNW-SSE striking faults and narrows to the west. The migration of the magmatic gases is mainly bound to the WSW-ENE striking Eger Rift main faults, while the younger NNW-SSE striking faults only have a distributive function. Southerly directed gas migration along the Horni Slavkov deep fault formed the small gas escape centre of Konstantinovy Lazne in the area of intersection with the Bezdruzice deep fault.
Keywords: gas flux; gas composition; He isotopes and gas fractionation; minerals springs and mofettes; tectonics; faults; Ohre (Eger) rift; Czech Republic